Ultrasmall BiOI Quantum Dots with Efficient Renal Clearance for Enhanced Radiotherapy of Cancer - Xin Wang; Zhao Guo; Chenyang Zhang; Shuang Zhu; Lele Li; Zhanjun Gu; Yuliang Zhao (Advanced Science, 2020)
Abstract Emerging strategies involving nanomaterials with high‐atomic‐number elements have been widely developed for radiotherapy in recent years. However, the concern regarding their potential toxicity caused by long‐term body retention still limits their further application. In this regard, rapidly clearable radiosensitizers are highly desired for practical cancer treatment. Thus, in this work, ultrasmall BiOI quantum dots (QDs) with efficient renal clearance characteristic and strong permeability inside solid tumor are designed to address this issue. Additionally, considering that injection methods have great influence on the biodistribution and radiotherapeutic efficacy of radiosensitizers, two common injection methods including intratumoral injection and intravenous injection are evaluated. The results exhibit that intratumoral injection can maximize the accumulation of radiosensitizers within a tumor compared to intravenous injection and further enhance radiotherapeutic efficacy. Furthermore, the radiosensitizing effect of BiOI QDs is revealed, which is not only attributed to the radiation enhancement of high‐Z elements but also is owed to the •OH production via catalyzing overexpressed H2O2 within a tumor by BiOI QDs under X‐ray irradiation. As a result, this work proposes a treatment paradigm to employ ultrasmall radiosensitizers integrated with local intratumoral injection to realize rapid clearance and high‐efficiency radiosensitization for cancer therapy.